2002
DOI: 10.1007/bf02817675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of berberine and (±)-bicuculline isolated fromCorydalis chaerophylla on spore germination of some fungi

Abstract: Berberine and (+/-)-bicuculline were isolated from roots and leaves, respectively, of Corydalis chaerophylla. Both were effective in vitro against spore germination of some plant pathogenic fungi (Alternaria brassicicola, A. brassicae, A. cheiranthi, A. melongenae, A. solani, Colletotrichum musae, C. falcatum, Curvularia penniseti, C. lunata, C. maculans, C. pallescens, Curvularia sp., Erysiphe pisi, E. cichoracearum, Erysiphe sp., Fusarium udum, Helminthosporium spiciferum, H. penniseti, H. frumentacei, Heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…This has been made possible by excessive and indiscriminate use of synthetic pesticides that have recently resulted in several ecological and human health problems (Maurya et al 2002;Miller 2004). Plant extracts and their active constituents have shown promising results against controlling several phytopathogenic fungi responsible for inciting severe plant diseases (Singh et al 1980(Singh et al , 1990Prithiviraj et al 1996Prithiviraj et al , 1997Basha et al 2002;Maurya et al 2001Maurya et al , 2002Singh et al 2010a-c). Singh et al (1995) and Prithiviraj et al (1998) successfully managed powdery mildew of pea (Pisum sativum) by application of ajoene, an active principle isolated from garlic (Allium sativum) and Neemazal from neem (Azadirachta indica).…”
Section: Introductionmentioning
confidence: 96%
“…This has been made possible by excessive and indiscriminate use of synthetic pesticides that have recently resulted in several ecological and human health problems (Maurya et al 2002;Miller 2004). Plant extracts and their active constituents have shown promising results against controlling several phytopathogenic fungi responsible for inciting severe plant diseases (Singh et al 1980(Singh et al , 1990Prithiviraj et al 1996Prithiviraj et al , 1997Basha et al 2002;Maurya et al 2001Maurya et al , 2002Singh et al 2010a-c). Singh et al (1995) and Prithiviraj et al (1998) successfully managed powdery mildew of pea (Pisum sativum) by application of ajoene, an active principle isolated from garlic (Allium sativum) and Neemazal from neem (Azadirachta indica).…”
Section: Introductionmentioning
confidence: 96%
“…They include the use of biocontrol agents (Vidhyasekaran and Muthamilan 1995), induced systemic resistance by natural products (Singh et al 1990(Singh et al , 1995Prithiviraj et al 1996Prithiviraj et al , 1997 and some microorganisms. Various extracts of medicinal plants have shown inhibitory effects against phytopathogenic fungi in vitro (Chaturvedi et al 1987;Sarma et al 1998Sarma et al , 1999Maurya et al 2001Maurya et al , 2002Basha et al 2002;Singh et al 2003). Among them, one of the medicinal plants, Argemone mexicana (Family: Papaveraceae), a common weed distributed throughout *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…109: 329-338, 2010. ß 2009 KEY WORDS: APOPTOSIS; BERBERINE; Akt; ASK1; ROS; p38 B BR, alkaloid isolated from Berberis species, is extensively studied for many years. The alkaloid has shown multiple biological and pharmacological activities such as antimicrobial activity [Basha et al, 2002;Hwang et al, 2003], anti-inflammatory agent [Fukuda et al, 1999;Lau et al, 2001], and anti-tumor activity Hwang et al, 2006;Lin et al, 2006]. Recently, it has been shown that BBR can cause apoptosis through a mitochondria-caspases-dependent pathway in human HepG2 cells [Hwang et al, 2006].…”
mentioning
confidence: 98%